The Universidad Cooperativa de Colombia: Between Locality and Globality - Vizcaíno G., Milcíades; Muñoz J., Ruth Edith (Cooperativismo & Desarrollo, 2013)
Problem: The Universidad Cooperativa de Colombia functions as an institution of higher education since 1970 and currently provides services in 18 campuses to 50,000 students with 4,800 teachers. The economic, social, political and cultural transformations of the last two decades have built a new stage called world system driven by globalization and powered by the second modernity or late modernity. Universities are in the process of adapting to this scenario. The thesis presented in this paper says that the Universidad Cooperativa de Colombia is located in the space between locality and globality without further integrating them into a single entity. Methodology: The paper is a reflection that discusses the global vs. local typology and rather put the discussion on a continuum from locality to globality. This reflection is based on information from the university relating it with other Colombian and Latin American universities and international organizations. Conclusion: the Universidad Cooperativa de Colombia must recognize its role both locally and in globality and, above all, integrate it into a single space in all its dimensions, with international indicators, as an institution of higher education.